Playing America's game : baseball, Latinos, and the color line - Burgos, Adrian, Jr., 1969- (American crossroads, 2007)
Latinos have been a significant presence in professional leagues from the beginning. Offering a study on Latinos and professional baseball since the 1880s, this book tells a compelling story of the men who negotiated the color line at every turn: passing as "Spanish" in the major leagues, or seeking respect and acceptance in the Negro leagues.